The vitamin D, ionised calcium and parathyroid hormone axis of cerebral capillary function: Therapeutic considerations for vascular-based neurodegenerative disorders - Lam, V.; Takechi, Ryu; Pallabage-Gamarallage, M.; Giles, C.; Mamo, John (Public Library of Science, 2015)
Blood-brain barrier dysfunction characterised by brain parenchymal extravasation of plasma proteins may contribute to risk of neurodegenerative disorders, however the mechanisms for increased capillary permeability are not understood. Increasing evidence suggests vitamin D confers central nervous system benefits and there is increasing demand for vitamin D supplementation. Vitamin D may influence the CNS via modulation of capillary function, however such effects may be indirect as it has a central role in maintaining calcium homeostasis, in concert with calcium regulatory hormones. This study utilised an integrated approach and investigated the effects of vitamin D supplementation, parathyroid tissue ablation (PTX), or exogenous infusion of parathyroid hormone (PTH) on cerebral capillary integrity. Parenchymal extravasation of immunoglobulin G (IgG) was used as a marker of cerebral capillary permeability. In C57BL/6J mice and Sprague Dawley rats, dietary vitamin D was associated with exaggerated abundance of IgG within cerebral cortex (CTX) and hippocampal formation (HPF). Vitamin D was also associated with increased plasma ionised calcium (iCa) and decreased PTH. A response to dose was suggested and parenchymal effects persisted for up to 24 weeks. Ablation of parathyroid glands increased CTX- and HPF-IgG abundance concomitant with a reduction in plasma iCa. With the provision of PTH, iCa levels increased, however the PTH treated animals did not show increased cerebral permeability. Vitamin D supplemented groups and rats with PTH-tissue ablation showed modestly increased parenchymal abundance of glial-fibrillary acidic protein (GFAP), a marker of astroglial activation. PTH infusion attenuated GFAP abundance. The findings suggest that vitamin D can compromise capillary integrity via a mechanism that is independent of calcium homeostasis. The effects of exogenous vitamin D supplementation on capillary function and in the context of prevention of vascular neurodegenerative conditions should be considered in the context of synergistic effects with calcium modulating hormones.